Potential of Natural Sweetener in Indonesia: A Systematic Review - Islamy, Muhammad Agung (Universitas Airlangga, 2024)
Natural sweetener is a food alternative to sugar obtained from nature through organic chemical processes that produce flavors and characteristics similar to sugar and synthetic sweeteners. This paper is made in the form of a systematic review to collect and identify data related to the potential of natural sweeteners in Indonesia. The writing was designed using PRISMA with PICO with outcomes of total solids, reducing sugar, Dextrose equivalent (DE), glycemic index (GI) as data selection methods. The data obtained showed 15 potential plants from 13 different articles or journals. After being classified, the majority of food ingredients are natural sweeteners of the saccharide type that have the potential to produce liquid sucrose, fructose syrup and glucose products. These product opportunities were selected based on plant commodities with the highest productivity such as cassava, corn, coconut, sugarcane, sweet potato, sago, taro, and sorghum from several regions such as West Java, Central Java, East Java, Riau, North Sumatra, West Sumatra, Lampung, South Sumatra, Central Kalimantan, West Nusa Tenggara, South Sulawesi, North Sulawesi, Gorontalo, Maluku, and Papua.